Padang Panjang City Inspectorate Strategy in Handling Community Complaints and Aspirations Through the Guardian Reporting Service - Halim, Muhammad Ajri; Putera, Roni Ekha; Kusdarini, Kusdarini; Putra, Roni Ekha (LPPM Universitas Ekasakti, 2023)
This research is motivated by the desire of the Padang Panjang City Government in realizing the achievement of the third mission of the city government which reads Improving responsive, innovative, and participatory governance. However, this will not be possible without joint efforts between the city government and the community, so that the government through the Padang Panjang Mayor Regulation Number 45 of 2020 concerning Guidelines for Management of Public Complaints Through Guardian Reporting Services in the Padang Panjang City Government, the Lapor Wali program was formed with the hope become a means of government in responding to the needs of conveying the aspirations of the people of Padang Panjang City. In this study, the theory used is strategy theory by Kotten. The method used is descriptive qualitative, with data collection techniques using interviews, documentation, and observation. The selection of informants was carried out using a purposive sampling technique. The results of this study conclude the strategy of the Padang Panjang Inspectorate in dealing with complaints and aspirations of the community through the guardian's report service has been carried out well although there are still some obstacles in handling it such as the inspectorate's communication with the related OPD is still not optimal.